2006
DOI: 10.1111/j.1365-2982.2006.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular interstitial cells of Cajal associated with mast cells survive nitrergic nerves in achalasia

Abstract: Achalasia is dominated by injury to inhibitory nerves. As intramuscular interstitial cells of Cajal (ICC-IM) are proposed to form functional units with nitrergic nerves, their fate in achalasia may be critically important. We studied the relationship between loss of nitrergic nerves and injury to ICC-IM in patients with achalasia and determined associations between ICC-IM and mast cells (MC), using quantitative immunohistochemistry and electron microscopy. Loss of neuronal nitric oxide synthase (nNOS) immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 42 publications
(42 reference statements)
9
75
0
Order By: Relevance
“…The hypothesis is that IL-9, secreted from mast cells, is one of the factors that promote ICC survival in human disease. We observed recently in esophageal tissue from patients with achalasia that there is a linear relationship between the number of surviving ICC and the number of mast cells that accumulate in the musculature [39]; piecemeal degranulation of mast cells making contact with ICC was abundant. Since mast cells can secrete IL-9 and stem cell factor [38] a positive influence of mast cells on ICC survival and/or repair seems possible.…”
Section: Discussionmentioning
confidence: 89%
“…The hypothesis is that IL-9, secreted from mast cells, is one of the factors that promote ICC survival in human disease. We observed recently in esophageal tissue from patients with achalasia that there is a linear relationship between the number of surviving ICC and the number of mast cells that accumulate in the musculature [39]; piecemeal degranulation of mast cells making contact with ICC was abundant. Since mast cells can secrete IL-9 and stem cell factor [38] a positive influence of mast cells on ICC survival and/or repair seems possible.…”
Section: Discussionmentioning
confidence: 89%
“…ICC are frequently surrounded by MC with established membrane-to-membrane contacts. Furthermore, the release of cytoplasmatic vesicles directed to ICC was observed (Zarate et al 2006). The cytoplasmatic vesicles in MC exhibited characteristic morphological changes defined as piecemeal degranulation that is thought to be associated with vesicle-mediated long-lasting release of the vesicle content (Dvorak et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence that MC may also contribute to smooth muscle activity and neural stimulation by releasing a variety of substances (Keith et al 1995, Corvera et al 1999, Hollenberg & Bunnett 1999, Reed et al 2003, Vodenicharov et al 2005. Histamines, prostaglandins and leukotrienes are potential paracrine signals in the communication pathways between MC and intrinsic (Zarate et al 2006). Ultrastructural analysis showed that i.m.…”
Section: Discussionmentioning
confidence: 99%
“…Myenteric denervation of the distal oesophagus extending into the stomach is characteristically seen at histological examination (Csendes et al 1992) and is selective for inhibitory nitric oxide (Mearin et al 1993;De Giorgio et al 1999;Zarate et al 2006) and vasoactive inhibitory polypeptide (Aggestrup et al 1983;Sigala et al 1995) releasing motor neurons resulting in unopposed excitatory activity. Familial, infectious, genetic and autoimmune mechanisms have all been postulated to contribute to the development of achalasia (Park et al 2005).…”
Section: Idiopathic Achalasiamentioning
confidence: 99%